2017
DOI: 10.1007/s11883-017-0656-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role for Cardiovascular Remodeling in Cardiovascular Outcomes

Abstract: These data highlight the benefits of certain guideline-directed medical therapies (GDMT) such as cardiac resynchronization therapy, surgical revascularization, and mechanical circulatory support on remodeling, while revealing the limitations of other therapies-routine mitral valve repair for patients with moderate ischemic mitral regurgitation and adjuncts to percutaneous coronary intervention in patients with ST elevation myocardial infarction (cyclosporine A and bioabsorbable cardiac matrix). The new angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 56 publications
0
28
0
1
Order By: Relevance
“…Our study analysed the impact of SV therapy on echocardiographic and clinic parameters of HFrEF outpatients previously treated with an optimal individualized pharmacological therapy which included ACEIs or ARBs, BBs and in most patients MRAs. Our main findings indicate that switching to SV induces incremental reverse remodelling, affecting both systolic and diastolic function, which could lead to a great impact on the progression and prognosis of HFrEF [6] . From baseline to 12 months follow-up we observed a progressive improvement of LVEF ( Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study analysed the impact of SV therapy on echocardiographic and clinic parameters of HFrEF outpatients previously treated with an optimal individualized pharmacological therapy which included ACEIs or ARBs, BBs and in most patients MRAs. Our main findings indicate that switching to SV induces incremental reverse remodelling, affecting both systolic and diastolic function, which could lead to a great impact on the progression and prognosis of HFrEF [6] . From baseline to 12 months follow-up we observed a progressive improvement of LVEF ( Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Sacubitril-valsartan (SV) is the first example of ARNIs and its safety and efficacy in chronic HFrEF patients were assessed in the PARADIGM-HF trial [5] . However, the property of SV to realize a reverse remodeling has not been extensively investigated so far, even if myocardial remodelling has shown to correlate with HF severity and demonstrated an important prognostic value [6] . Three clinical studies and a metanalysis showed a further improvement of cardiac reverse remodelling with SV compared to ACEi or ARBs [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac remodelling involves first of all increased left ventricular mass (LVM), which often causes cardiovascular complications [4,5]. As soon as in three months following myocardial revascularization, the patients manifested with the left ventricular (LV) remodelling [6,7].…”
Section: Conclusionrevascularization Contributed To a Considerably mentioning
confidence: 99%
“…Cardiac remodeling (CR) is a complex process involving cardiac myocyte growth and death, vascular rarefaction, fibrosis, inflammation, and electrophysiological alterations (Burchfield et al, 2013 ; Xie et al, 2013 ). CR can be conceptualized as a set of cellular, cardiac and interstitial changes in the heart, manifested clinically by changes in the size, mass (hypertrophy and atrophy), geometry (wall thickness and heart shape) and function, in response to a given stimulus—it is one of the major responses of the heart to biomechanical stresses and pathological stimuli (Zornoff et al, 2009 ; Gajarsa and Kloner, 2011 ; Braunwald, 2013 ; Heusch et al, 2014 ; Sekaran et al, 2017 ). We can also detect the presence of scarred areas, fibrosis and inflammatory infiltrate.…”
Section: Introductionmentioning
confidence: 99%